2021
DOI: 10.3390/ijerph18094880
|View full text |Cite
|
Sign up to set email alerts
|

Relative Contribution among Physical Fitness Factors Contributing to the Performance of Modern Pentathlon

Abstract: This study reveals the relationship between physical fitness factors and performance in modern pentathlon and identifies the contribution of each physical factor to overall performance. The physical fitness assessment data and the competition records collected by the Korean national team pentathletes for the years 2005 to 2019 were tracked. The correlation between the competition records and fitness factors was confirmed by correlation analysis. In addition, the physical factors affecting performance were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…We observed that 1RM of squat was improved after completing both RT and CT, and after CT, the IMTP was significantly improved. Squat and IMTP mainly reflect lower-limb strength for quadriceps femoris and hamstring, which are linked to the performance of modern pentathlon athletes ( Ko et al, 2021 ). The traditional RT focuses only on isometric contraction with slow velocity, and the conversion time between eccentric contraction and concentric contraction becomes longer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that 1RM of squat was improved after completing both RT and CT, and after CT, the IMTP was significantly improved. Squat and IMTP mainly reflect lower-limb strength for quadriceps femoris and hamstring, which are linked to the performance of modern pentathlon athletes ( Ko et al, 2021 ). The traditional RT focuses only on isometric contraction with slow velocity, and the conversion time between eccentric contraction and concentric contraction becomes longer.…”
Section: Discussionmentioning
confidence: 99%
“…Lower-limb strength and power are one of the most important contributors to the performance of modern pentathlon ( Chirico et al, 2019 ). Ko et al (2021) observed that, for example, lower-limb strength and power (e.g., the average strength of flexor muscle and extensor muscle, squat, and sergeant jump) is the most relevant predictor of overall modern pentathlon performance, especially in the fencing, swimming, and laser-run.…”
Section: Introductionmentioning
confidence: 99%